サブストームのオンセット過程 - 森岡, 昭; 三好, 由純; 笠羽, 康正; 佐藤, 夏雄; 門倉, 昭; 三澤, 浩昭; 宮下, 幸長; Akira, Morioka; Yoshizumi, Miyoshi; Yasumasa, Kasaba; N., Sato; Akira, Kadokura; et al. (2013)
第4回極域科学シンポジウム 個別セッション：[OS] 宙空圏 11月14日（木） 国立極地研究所 ２階大会議室 conference object